Relationship between histological damage, viral load and serum transaminase levels in patients with chronic hepatitis C - Emin ALTIPARMAK,; Ülkü SARITAŞ,; Engin ALTINTAŞ,; Ali TÜREYEN,; Dilek OĞUZ,; Tülin ŞAHİN, (Turkish Journal of Gastroenterology, 2019)
-